2017
DOI: 10.3389/fphar.2017.00641
|View full text |Cite
|
Sign up to set email alerts
|

TC299423, a Novel Agonist for Nicotinic Acetylcholine Receptors

Abstract: (E)-5-(Pyrimidin-5-yl)-1,2,3,4,7,8-hexahydroazocine (TC299423) is a novel agonist for nicotinic acetylcholine receptors (nAChRs). We examined its efficacy, affinity, and potency for α6β2∗ (α6β2-containing), α4β2∗, and α3β4∗ nAChRs, using [125I]-epibatidine binding, whole-cell patch-clamp recordings, synaptosomal 86Rb+ efflux, [3H]-dopamine release, and [3H]-acetylcholine release. TC299423 displayed an EC50 of 30–60 nM for α6β2∗ nAChRs in patch-clamp recordings and [3H]-dopamine release assays. Its potency for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Additionally, we conducted locomotor assays to determine the effects of acute farnesene treatment on locomotor behavior in male and female mice. It is well understood that nicotine increases locomotor activity in mice ( Wall et al, 2017 ), and was recently determined that green apple flavorant, farnesol, also increased this behavior ( Avelar et al, 2019 ). Here, male and female mice were administered intraperitoneal injections of saline or 0.1 mg/kg farnesene, and locomotor activity was assessed in an open field test ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we conducted locomotor assays to determine the effects of acute farnesene treatment on locomotor behavior in male and female mice. It is well understood that nicotine increases locomotor activity in mice ( Wall et al, 2017 ), and was recently determined that green apple flavorant, farnesol, also increased this behavior ( Avelar et al, 2019 ). Here, male and female mice were administered intraperitoneal injections of saline or 0.1 mg/kg farnesene, and locomotor activity was assessed in an open field test ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The development of new agents with affinities and potencies better than nicotine and other commercially available compounds is critical to further understanding nAChR involvement in the addiction process. We have seen further characterization of the “TC” compounds as high-affinity nAChR compounds [ 28 , 29 ]. Collectively, there is a lack of 6/ 2* subtype-selective agents that could be useful in treating addiction-related or neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…α 4* but not α 6* nAChRs regulate nicotine-induced bursting of VTA dopamine neurons ( Exley et al, 2011 ). The novel α 6 β 2* nAChR agonist TC299423 induced only modest rewarding effects in wild-type, which were enhanced in α 6 gain-of-function mutant mice ( Wall et al, 2017 ). However, TC299423 had no-effects, no-intravenous-nicotine self-administration in rats ( Wall et al, 2017 ).…”
Section: Dopamine Mechanisms Of Nicotine Rewardmentioning
confidence: 99%
“…The novel α 6 β 2* nAChR agonist TC299423 induced only modest rewarding effects in wild-type, which were enhanced in α 6 gain-of-function mutant mice ( Wall et al, 2017 ). However, TC299423 had no-effects, no-intravenous-nicotine self-administration in rats ( Wall et al, 2017 ). Using an intra-VTA self-administration procedure, it was shown that α 6 nAChR subunit knockout mice will self-administer similar quantities of nicotine in the VTA as wild-type mice, whereas α 4 subunit knockout mice self-administer far less nicotine ( Exley et al, 2011 ).…”
Section: Dopamine Mechanisms Of Nicotine Rewardmentioning
confidence: 99%